Comparison of the Incidence of Blood Disorders in Urological Cancer Patients Undergoing Chemotherapy at Dr. Pirngadi Hospital, Medan City - Hasroni Fathurrahman; Syahril Ananda Siregar (UMSU, 2026)
Introduction: Blood disorders such as anemia, leukopenia, and thrombocytopenia are common in urological cancer patients undergoing chemotherapy. This study aims to compare the incidence of blood disorders between patients with bladder cancer, testicular cancer, prostate cancer, and penile cancer who undergo chemotherapy at Dr. Pirngadi Hospital Medan City. Methods: This study used a retrospective design with comparative analysis. Data were taken from the medical records of patients who underwent chemotherapy during the 2019-2023 period. The sample consisted of 72 patients, namely 50 bladder cancer patients, 10 testicular cancer patients, 7 prostate cancer patients, and 5 penile cancer patients. Data were analyzed using descriptive statistical tests and analysis. Kruskal-Wallis Test. Results: showed that a decrease in hemoglobin was the most common blood disorder, especially in penile (100%) and bladder (84.6%) cancers. Leukopenia is rare, while leukocytosis is more commonly found, especially in penile cancer (60%). Platelet disorders were dominant in bladder cancer, with a decrease and increase of 12.8% each. The Kruskal-Wallis test showed no significant difference in the decrease in hemoglobin, leukocytes, or platelets between types of urological cancer (p 0.05), except for an increase in hemoglobin which showed a significant difference (p 0.05). Conclusions: there was no significant difference in blood disorders between types of urological cancer, although haematological monitoring remains important to prevent chemotherapy complications.